1998
DOI: 10.1099/0022-1317-79-10-2319
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the P1 protein of potato Y potyvirus in association with cytoplasmic inclusion bodies and in the cytoplasm of infected cells.

Abstract: The N-terminal P1 proteinase of potato virus Y (ordinary strain group isolate PVY-O) was expressed in E. coli. Antiserum was raised against the expressed protein and used to detect the viral proteins in infected tobacco leaf tissue by Western blotting and by electron microscopy with immunogold labelling. In the immunogold localization studies P1 protein was detected in association with the cytoplasmic inclusion bodies characteristic of PVY infections and in the cytoplasm of the infected plant cells. No signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
5
14
0
Order By: Relevance
“…However, parallel to this information, it has also been asserted that neither of these two proteins appears to be required for cell-to-cell movement. Arbatova et al (1998) later indirectly confirmed this assertion. Immunogold localization of PVY P1 protein in infected plants showed an absence of this protein in the cell wall and plasmodesmata (Arbatova et al 1998).…”
Section: P1 and Its Activity In Viral Cell-to-cell Movementssupporting
confidence: 72%
See 3 more Smart Citations
“…However, parallel to this information, it has also been asserted that neither of these two proteins appears to be required for cell-to-cell movement. Arbatova et al (1998) later indirectly confirmed this assertion. Immunogold localization of PVY P1 protein in infected plants showed an absence of this protein in the cell wall and plasmodesmata (Arbatova et al 1998).…”
Section: P1 and Its Activity In Viral Cell-to-cell Movementssupporting
confidence: 72%
“…Arbatova et al (1998) later indirectly confirmed this assertion. Immunogold localization of PVY P1 protein in infected plants showed an absence of this protein in the cell wall and plasmodesmata (Arbatova et al 1998). On the other hand, we need to mention the situation in the sobemoviruses.…”
Section: P1 and Its Activity In Viral Cell-to-cell Movementssupporting
confidence: 72%
See 2 more Smart Citations
“…6A) and the mutationally changed polarity and acidic property, respectively, of these positions implied their criticality. P1 protein's involvement in genome amplification has been suggested for Tobacco etch virus (TEV) (Verchot and Carrington 1995) and Potato virus Y (PVY) (Arbatova et al 1998). Its RNA-binding activity has been attributed to its specific structure and ionic interaction with the phosphate backbone of viral RNA (Brantley and Hunt 1993;Merits et al 1998).…”
Section: Discussionmentioning
confidence: 99%